Cybersecurity Challenges and Solutions in the Fintech Mobile App Ecosystem - Ishamuddin Mustapha; Vaicondam, Yamunah; Agha Jahanzeb; Burkhanov Aktam Usmanovich; Binti Yusof, Siti Hawa (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The rapid growth of the fintech industry, driven by the proliferation of mobile applications, has revolutionized financial services, providing unprecedented convenience to users. However, this innovation comes with inherent cybersecurity challenges that demand rigorous attention. This study delves into the complex and ever-evolving landscape of cybersecurity within the fintech mobile app ecosystem, aiming to identify challenges and present viable solutions. Cybersecurity threats in the fintech mobile app ecosystem encompass a broad spectrum, including data breaches, malware attacks, phishing schemes, and identity theft. As fintech apps handle sensitive financial data and transactions, they are prime targets for malicious actors seeking financial gain. To address these threats, this research examines current cybersecurity strategies and emerging technologies, such as advanced encryption, biometric authentication, and AI-driven anomaly detection. Furthermore, regulatory frameworks and industry standards play a crucial role in shaping cybersecurity practices within fintech. This study assesses the impact of compliance requirements on fintech companies and their ability to protect user data. Real-world case studies and incident analyses provide valuable insights into the consequences of cybersecurity breaches in this sector. Ultimately, this research aims to contribute to a comprehensive understanding of the multifaceted cybersecurity challenges faced by the fintech mobile app ecosystem and offers practical recommendations for fintech firms, regulators, and cybersecurity professionals to enhance security measures. Strengthening the security foundation is paramount to sustaining user trust, fostering continued innovation, and securing the future of mobile fintech.